Paleodietary Analysis of Human Remains from a Hellenistic-Roman Cemetery at Camihöyük, Turkey. (14th March 2013) - İzci, Yusuf and Kaya, Serdar and Erdem, Onur and Akay, Cemal and Kural, Cahit and Soykut, Buğra and Başoğlu, Okşan and Şenyurt, Yücel and Kılıç, Selim and Temiz, Çaglar
Abstract : The presence of copper, zinc, magnesium, iron, lead, molybdenum, manganese and nickel was discovered on 22 human ribs in a Hellenistic-Roman cemetery located in the ancient city of Camihöyük, Turkey. The levels of each element found in the males were higher than those in females, except iron. Copper, magnesium, iron, molybdenum, and nickel levels were measured to be higher in the soil than in the skeletons, whereas the other elements were higher in the human skeletons. Lead was not traced in the soil, but on the skeletons. These individuals had probably been exposed to this element during their lives due to higher consumption of vegetables than meat.